Market Value Added Among Historiecal Cost and Fair Value Contravercy (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Because of the vulnerability of the concept of historical cost adopted as a basis for accounting measurement to many of the criticisms in reaction counter to the concept of fair value, the aim of the research is to try to make a comparison between the historical cost and fair value to prove the health and safety of any of the measurement best for the preparation of financial statements and through the state of each of the two study secretary and good financial investment after being diagnosed with a realistic problem is the limitations of the concept of historical cost in the evaluation of assets in spite of the supposed information disclosed in the financial statements compared to appropriate property for the concept of the fair value of the decisions of its users to re-evaluate investments one at a financial adoption of the added market value between the dialectic of the concept of historical cost Reliability and fair value Has been to reach a set of conclusions that the fair value of the most important in the preparation of financial statements are complementary to those that are prepared under the historical cost which affects the increase of accounting disclosure